The Relationship Between Gadget Use and Sleep Patterns Among Teenagers at SMA PGRI 2 Denpasar - Ni Putu Sriarta Prabhadewi; I Gusti Ketut Gede Ngurah; I Wayan Suardana; I Ketut Gama; Agus Sri Lestari; Ketut Sudiantara; Komang Ayu Henny Achjar; I Gusti Ayu Harini; Ni Nyoman Hartati; I Wayan Mustika (Health Dynamics, 2025)
Background: Excessive gadget use among adolescents may disrupt sleep patterns and reduce sleep quality. Blue light exposure and stimulating digital activities before bedtime can interfere with circadian rhythms and delay sleep onset. This study aimed to examine the relationship between gadget use and sleep patterns among students at SMA PGRI 2 Denpasar. Methods: A cross-sectional quantitative design was employed, involving 145 students aged 14–19 years selected through simple random sampling. Data were collected via online questionnaires assessing gadget usage (duration and frequency) and sleep behaviors (sleep duration, quality, and disturbances). Spearman Rank correlation was used for statistical analysis. Results: Most respondents used gadgets for more than 2.5 hours daily, especially before bedtime. While 69.0% reported appropriate gadget use duration, 86.9% experienced poor sleep patterns. A significant negative correlation was found between gadget use duration and sleep patterns (r = –0.270; p = 0.001), indicating that longer usage was associated with poorer sleep. However, the frequency of gadget use showed a weak, non-significant positive correlation (r = 0.127; p = 0.129). Conclusion: Gadget use duration significantly affects adolescent sleep patterns, while usage frequency does not. Sleep hygiene education and behavioral interventions are recommended to reduce bedtime gadget use and improve sleep quality.